Identification of the Crucial Role of CCL22 in F. nucleatum-Related Colorectal Tumorigenesis that Correlates With Tumor Microenvironment and Immune Checkpoint Therapy - Wang, Hufei; Luo, Kangjia; Guan, Zilong; Li, Zhi; Xiang, Jun; Ou, Suwen; Tao, Yangbao; Ran, Songlin; Ye, Jinhua; Ma, Tianyi; Qiao, Tianyu; Zhang, Zhiming; et al. (Frontiers in Genetics, 2022)
Colorectal cancer (CRC) is the third most common malignant cancer worldwide with the second highest mortality. Gut microbiota can educate the tumor microenvironment (TME), consequently influencing the efficacy of immune checkpoint inhibitors (ICIs). Fusobacterium nucleatum is one of the most crucial bacteria contributing to colorectal tumorigenesis, but the molecular mechanisms between F. nucleatum and TME or ICIs are poorly investigated. In the present study, we firstly analyzed differentially expressed genes and the biological functions between F. nucleatum-infected and uninfected CRC cell lines, with the findings that CCL22 mRNA expression was markedly upregulated after F. nucleatum infection. Moreover, the survival analysis showed that CCL22 was significantly associated with the overall survival of CRC patients. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analysis suggested that CCL22 was related to immune-related terms. Furthermore, the ESTIMATE analysis indicated that the high-CCL22-expression subgroup had a higher immune/stromal/estimate score and lower tumor purity. The CIBERSORT analysis indicated that the high-CCL22-expression group had more immune-suppressive cells and less antitumor immune cells. In addition, immune checkpoint genes and cytotoxic genes were positively correlated with CCL22 expression. The immunophenoscore analysis suggested that CCL22 was associated with the IPS-CTLA4 and PD1/PD-L1/PD-L2 score. Interestingly, CCL22 expression in the KRAS and APC mutation groups was markedly reduced compared to that of the wild groups. In summary, our study provided evidence that CCL22 might play a crucial role in F. nucleatum-related colorectal tumorigenesis and correlate with TME and ICIs, which deserves further study.